2021
DOI: 10.1242/jcs.252221
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular responses to adhesive interactions with galectin-8- and fibronectin-coated substrates

Abstract: The mechanisms underlying the cellular response to extracellular matrices (ECM), consisting of multiple adhesive ligands, are still poorly understood. Here we address this topic by monitoring the differential cellular response to two different extracellular adhesion molecules – fibronectin, a major integrin ligand, and galectin-8, a lectin, that binds β-galactoside residues, as well as to mixtures of the two proteins. Cell spreading on galectin-8 coated substrates results in a larger projected cell area, a mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…VSMCs cultured on fibronectin-coated surface recruit more vinculin clustering in FA ( Figure 4A ), which was consistent with the previous finding demonstrating protein clusters in FA in the cells cultured on the fibronectin-coated surface. 52 Since WGA conjugates are commonly used as markers for glycoproteins on the plasma membrane and the trans-Golgi in the cytoplasm, 53 the peri-nucleus condensation of WGA signal ( Figure 4B ) is consistent with the previous finding of trans-Golgi clustering in response to cyclic strain. 54 …”
Section: Discussionsupporting
confidence: 87%
“…VSMCs cultured on fibronectin-coated surface recruit more vinculin clustering in FA ( Figure 4A ), which was consistent with the previous finding demonstrating protein clusters in FA in the cells cultured on the fibronectin-coated surface. 52 Since WGA conjugates are commonly used as markers for glycoproteins on the plasma membrane and the trans-Golgi in the cytoplasm, 53 the peri-nucleus condensation of WGA signal ( Figure 4B ) is consistent with the previous finding of trans-Golgi clustering in response to cyclic strain. 54 …”
Section: Discussionsupporting
confidence: 87%
“…Taking into account the outcomes for invadopodia formation assessed separately for collagens type I and IV, it indicates that the effects observed for complex ECM compositions cannot be directly extrapolated from the observations done for a single ECM protein. This was also seen in the study on cells' spreading and adhesion properties on galectin-8 and fibronectin and their combinations at different ratios [74]. Summarizing this section, it is crucial to state that GSN is apparently important for the proper functioning of invadopodia as it resides there.…”
Section: Invasion Potentialmentioning
confidence: 74%
“…This hypothesis is worth evaluation in future studies. Recently, Li with colleagues showed that filopodial activity is important for cell spreading and adhesion on fibronectin and galectin-8 [74]. However, they noticed that the cells spreading over galectin-8 formed a higher number of filopodia (but no stress fibers and focal adhesions) in comparison to the cells cultured on fibronectin.…”
Section: Invasion Potentialmentioning
confidence: 99%
“…These include the promotion of homotypic aggregation of the tumor cells as well as increased cell–matrix interactions that increase cell growth, adhesion, and selective metastatic seeding [ 37 , 38 , 104 ]. This can be attributed to the role of Gal-8 as an extracellular matrix protein, equipotent to fibronectin in promoting cell adhesion, spreading, and migration [ 10 , 12 ]. Accordingly, Gal-8 silencing inhibits filopodia formation [ 12 ], and aggregation of cancer cells [ 37 ]; processes that are actively engaged in metastatic progression.…”
Section: Gal-8 Cytokines and Cancermentioning
confidence: 99%
“…synovial fluids of RA patients (25-60 nM) [7] or serum of breast (4.7-233.2 ng/ ml) and colon (5.6-178.2 ng/ml) cancer patients [8]). Extracellular Gal-8 promotes cell adhesion upon binding to cell adhesion molecules such as integrins [9][10][11][12][13], CD44 [7], CD166 [14], and Podoplanin [15].…”
Section: Introductionmentioning
confidence: 99%